Roads, travelling and communication in the Polish-Lithuanian commonwealth in the 18th century. Russian and West European visitors` perspective = Drogi, podróżowanie i funkcjonowanie poczty w Rzeczypospolitej Obojga Narodów w XVIII w. Z perspektywy przybyszy z Rosji i państw Europy zachodniej - Ciesielski, Tomasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents the technical condition of roads, waterways, bridges, levees and other engineering structures in Poland based on accounts of visitors from Russia and other foreign countries. It discusses land and water means of transport were discussed along with the quality of service offered by Polish and Lithuanian inns which were valued very poorly by all foreigners. In the 18th century, travelling and communication in the Polish-Lithuanian Commonwealth was a truly fascinating issue.
Keywords: the Eighteenth Century; the Polish-Lithuanian Commonwealth; roads; travelling; communication; post; travels; Russian visitors in Poland and Lithuania; visitors from countries of western Europe in Poland and Lithuania; Rzeczpospolita Obojga Narodów; droga; podróżowanie; komunikacja; poczta; podróżnicy; Rosjanie w Polsce i na Litwie; przybysze z zachodniej Europy w Polsce i na Litwie; 18 w.